3D structured Mn2O3 synthesized using tween surfactant: influence on the morphology and oxygen reduction catalytic performance. Issue 3 (5th December 2018) - Fang, Yuan; Wang, Yonghui; Wang, Fen; Zhu, Jianfeng
Abstract : Tween-80 affects the oxygen vacancies of Mn2 O3, boosting its oxygen storage capability and electron transfer rate for ORR. Abstract : 3D structured Mn2 O3 with flower-like (Mn2 O3 -F), globe-like (Mn2 O3 -G) or rhombohedral (Mn2 O3 -R) morphologies were successfully synthesized by solvothermal method by controlling the amounts of Tween surfactant. These Mn2 O3 oxides enhance the catalytic activity for the oxygen reduction reaction (ORR) in direct methanol fuel cells (DMFCs) significantly, while PtRu/C works as the anode catalyst and polymer fiber membrane (PFM) functions as the electrolyte film. Mn2 O3 -G shows higher ORR catalytic activity than Mn2 O3 -F and Mn2 O3 -R. The maximum power density ( P max ) of Mn2 O3 -F-, Mn2 O3 -G- and Mn2 O3 -R-based DMFCs are 11.44, 21.03 and 10.22 mW cm −2 at room temperature, respectively. The influence of the Tween surfactant on the microstructure and ORR properties were also studied systematically. Compared with Mn2 O3 -F and Mn2 O3 -R, the Raman and XPS results indicate that Mn2 O3 -G has more oxygen vacancies, which can promote the electrical conductivity and act as an active center to absorb and store available O2 for stable ORR properties.